Inverse sum indeg coindex of graphs - Pattabiraman, K. (Carpathian Mathematical Publications, 2019)
The inverse sum indeg coindex $\overline{ISI}(G)$ of a simple connected graph $G$ is defined as the sum of the terms $\frac{d_G(u)d_G(v)}{d_G(u)+d_G(v)}$ over all edges $uv$ not in $G,$ where $d_G(u)$ denotes the degree of a vertex $u$ of $G.$ In this paper, we present the upper bounds on inverse sum indeg coindex of edge corona product graph and Mycielskian graph. In addition, we obtain the exact value of both inverse sum indeg index and its coindex of a double graph.